Fire monitoring radio channel system for protected facilities and public notificatioin in the Arctic zone - V.S. Butko; V.I. Zykov; T.A. Lomaeva; A.I. Fursov (Российская Арктика)
The article discusses the issues of substantiating the need to increase the level of fire protection of critical facilities in the Arctic zone of the Russian Federation through the use of wireless fire safety monitoring systems for protected facilities and public notification. Such systems make it possible to monitor the fire-fighting condition of protected objects with a high degree of reliability, significantly increase the responsiveness to fires and emergencies due to the transmission of data on the state of protected objects in real time.